Dielectric Physics of Phospholipid Monolayers by Maxwell Displacement Current Measurement and Langmuir Technique - Sulaiman, Khaulah @ Che Som (Malaysian Journal of Science, 2005)
Dielectric Physics of Phospholipid Monolayers by Maxwell Displacement Current Measurement and Langmuir Technique